2017
DOI: 10.1136/jech-2017-209769
|View full text |Cite
|
Sign up to set email alerts
|

Operationalisation and validation of the Stopping Elderly Accidents, Deaths, and Injuries (STEADI) fall risk algorithm in a nationally representative sample

Abstract: Background Preventing falls and fall-related injuries among older adults is a public health priority. The Stopping Elderly Accidents, Deaths, and Injuries (STEADI) tool was developed to promote fall risk screening and encourage coordination between clinical and community-based fall prevention resources; however, little is known about the tool’s predictive validity or adaptability to survey data. Methods Data from five annual rounds (2011–2015) of the National Health and Aging Trends Study (NHATS), a represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 38 publications
1
45
0
3
Order By: Relevance
“…A major strength of this study was the inclusion of several falls‐related questions and a combination of self‐reported and performance‐based measures of physical functioning, enabling use of the CDC STEADI algorithm in a nationally representative sample of older adults. There are some differences between the physical function measures used in NHATS and those recommended in the CDC STEADI toolkit that might result in misclassification of fall‐risk, but the validity of using the NHATS physical performance measures to adapt the STEADI algorithm and predict future falls was previously demonstrated …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major strength of this study was the inclusion of several falls‐related questions and a combination of self‐reported and performance‐based measures of physical functioning, enabling use of the CDC STEADI algorithm in a nationally representative sample of older adults. There are some differences between the physical function measures used in NHATS and those recommended in the CDC STEADI toolkit that might result in misclassification of fall‐risk, but the validity of using the NHATS physical performance measures to adapt the STEADI algorithm and predict future falls was previously demonstrated …”
Section: Discussionmentioning
confidence: 99%
“…There are some differences between the physical function measures used in NHATS and those recommended in the CDC STEADI toolkit that might result in misclassification of fall-risk, but the validity of using the NHATS physical performance measures to adapt the STEADI algorithm and predict future falls was previously demonstrated. 23 Deaths attributable to falls in the United States increased by 31% between 2007 and 2016, and fall-related mortality increased the most in the oldest old. 24 Improvements in screening and referrals to evidence-based programs, including community-based fall prevention programs, exercise, and rehabilitation, are a critical component of reducing the alarming upward trend in fallrelated mortality, 25,26 The Medicare-sponsored annual wellness visit is a primary opportunity to conduct a fallrisk screening.…”
Section: Discussionmentioning
confidence: 99%
“…risk and to coordinate clinical and community-based fall prevention initiatives are warrant (Lohman et al, 2017). Johnston et al (2019) recently demonstrated that the implementation of STEADI fall risk screening and prevention strategies among older adults in primary care settings could reduce fallrelated hospitalizations and lower the associated health care costs (Johnston et al, 2019) .…”
Section: Discussionmentioning
confidence: 99%
“…For individuals aged 65-74, the prevalence of falls was 67.1%, and for those older than 75, it was 78.2% (Health Research and Development Agency, 2013). The Fall Risk Instruments that widely use, are include Stopping Elderly Accidents, Deaths, & Injuries (STEADI) Initiative from the Centers for Disease Control and Prevention (CDC) and The Johns Hopkins Fall Risk Assessment Tool (JHFRAT) from the Johns Hopkins University (Poe et al, 2007;Karakiewicz, 2015;Lohman et al, 2017;Hojati, risk instruments in some countries are develop by by JHFRAT (Thiamwong et al, 2008). However, a few researchers used it to predict fall risk for the Indonesia elderly.…”
Section: Introductionmentioning
confidence: 99%
“…This situation can influence a different health condition than of those who are not enrolled in a FHS, both fall prevention initiatives. (21) Therefore, the nurse must be prepared to assist in the prevention of falls, to use fall screening tools and to orient the patient to maintain a safe environment and correctly take their medications.…”
Section: Discussionmentioning
confidence: 99%